PERSEPSI SISWA IPS TERHADAP JURUSAN IPS DI SMA NEGERI 1 PEKANBARU - ", Azura; Asriwandari, Hesti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
The purpose of this research is to know the relationship between : (1) student’s learning achievement and student’s perception towards social science majors, (2) interest in placement and student’s perception towards social science majors, (3) motivation and student’s perception towards social science majors, (4) student’s learning achievement, interest in placement, motivation and student’s perception towards social science majors in high school 1 Pekanbaru. This research is done in high school 1 Pekanbaru 7 January – 10 January 2019. The type of research conducted is descriptive quantitative research. The data were gathered by questionnaire method, observation and documentation. The population of research was 58 student’s and a sample of 50 student’s was taken based on the amount of N that has been applied to the indigo distribution rtabel with a significant amount 5%. While the data analysis was product moment correlation analysis and double regression with the level signification of (α) 5%. Based on the data analysis it concludes. (1) there is correlation betwen student’s learning achievement and student’s perception towards social science majors, which had been proven by the correlation coefficient (r) 0,291 significant 0,040, (2) there is correlation betwen interest in placement and student’s perception towards social science majors, which had been proven by the correlation coefficient (r) 0,739 significant0,00, (3) motivation and student’s perception towards social science majors, which had been proven by the correlation coefficient (r) 0,740 significant 0,00, (4) student’s learning achievement, interest in placement, motivation and student’s perception towards social science majors in high school 1 Pekanbaru, which had been proven by the correlation coefficient (R) 0,675 significant 0,00.Keywords: Student’s Learning Achievement, Interest, Motivation and Perception